A longitudinal macro analysis of social determinants of health and their impacts on HIV prevalence and nutritional deficiencies in Sub-Saharan Africa - Mzolisi Abednigo Payi; Dominic Abaver; Teke Apalata (Acta Psychologica)
Sub-Saharan Africa faces a dual public health crisis of HIV and nutritional deficiencies driven by profound socio-economic disparities. Despite significant micro-study research, macro-level, longitudinal patterns and causal dynamics remain underexplored. This study employs Panel Auto-regressive distributed lags, Panel Granger causality, and Vector auto-correction model to examine the influence of social determinants on HIV prevalence and nutritional deficiencies across Sub-Saharan Africa. The study further carried out robustness diagnostics using Driscoll – Kraay standard error regression to confirm the reliability of the results. For HIV prevalence, income, education, and employment reduce rates over the long term, while healthcare access and housing quality show positive associations. Short-term effects show the benefits of income and healthcare access, with other factors showing limited impact. For nutritional deficiencies, income, education, employment, and housing quality significantly reduce malnutrition in the long term, while healthcare access correlates positively. Short-term effects show the immediate role of income and housing quality. The causal results show unidirectional links between income, education, employment, and housing quality to HIV. Housing quality and income exhibit bidirectional causality. No causal link exists between HIV and nutritional deficiencies. The study recommends the need for income support programs, expanded educational access, skill development, and strengthened healthcare systems.